Southern African Geomorphology Recent Trends and New Directions - Meadows, Michael; Holmes, Peter (UJ Press, 2013)
This book covers the geomorphology and landscape evolution of South Africa, focusing on arid landscapes, fluvial systems, karst, Quaternary landscapes, macro-scale geomorphic evolution, coastal geomorphology and applied geomorphology. It would appeal to postgraduate students in Physical Geography (Geomorphology) and Physical Geology and all academics in the earth sciences.